The “creme brulee” sampler: a new high-resolution method for the fast vertical sampling of intertidal fine sediments - Laviale, Martin
The reduced depth of the photic zone in most intertidal and shallow coastal sediments makes the characterization of its properties a considerable methodological challenge. Availablemethods for sediment sampling present insufficient resolution (ca. 2 mm) for sedimentary biofilms or require considerable post-sampling handling and operator expertise. In this study, we describe a new cryo-sampling device allowing the collection of sediment vertical sections as thin as 250 μm in a fast, inexpensive and reliable way. The method was validated by quantifying common sediment physical properties (mass, water content) of samples of different thicknesses (from 250 μmto 2mm) collected fromdifferent sampling sites (mud and sandy-mud sediments) by operatorswith different levels of training. Its usefulness was demonstrated by characterizing the short-term dynamics of microphytobenthos biomass (chlorophyll a content) during a typical vertical migratory event. Results emphasize the importance of choosing the sample thicknessmatching the dynamic processes under study in intertidal sediments. This device opens promising perspectives in studies susceptible to generate a large number of samples and where the fine-scale properties of the surface sediment are of importance.